Iodine–Iodine Bonding makes Tetra(diiodine)chloride, [Cl(I2)4]−, Planar1. Issue 48 (2nd October 2013) - Walbaum, Christine; Richter, Mark; Sachs, Ulf; Pantenburg, Ingo; Riedel, Sebastian; Mudring, Anja‐Verena; Meyer, Gerd
<x xml:space="preserve">Abstract</x> All square: The polyinterhalide [Cl(I2)4]− is square‐planar in the crystal structure of [(H5O2)(I2b15c5)2][Cl(I2)4] (I2b15c5=diiodobenzo‐15‐crown‐5), although it would be tetrahedral in the gas phase. Along with other effects, such as electrostatic attractions between the cationic and planar anionic layers, iodine–iodine bonding with σ‐hole interactions plays a considerable role is stabilizing the square‐planar configuration.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>